Reactive oxidative species (ROS)-based nanomedicine for BBB crossing and glioma treatment: current status and future directions - Wu, Dandan; Chen, Xuehui; Zhou, Shuqiu; Li, Bin (Frontiers in Immunology, 2023)
Glioma is the most common primary intracranial tumor in adults with poor prognosis. Current clinical treatment for glioma includes surgical resection along with chemoradiotherapy. However, the therapeutic efficacy is still unsatisfactory. The invasive nature of the glioma makes it impossible to completely resect it. The presence of blood-brain barrier (BBB) blocks chemotherapeutic drugs access to brain parenchyma for glioma treatment. Besides, tumor heterogeneity and hypoxic tumor microenvironment remarkably limit the efficacy of radiotherapy. With rapid advances of nanotechnology, the emergence of a new treatment approach, namely, reactive oxygen species (ROS)-based nanotherapy, provides an effective approach for eliminating glioma via generating large amounts of ROS in glioma cells. In addition, the emerging nanotechnology also provides BBB-crossing strategies, which allows effective ROS-based nanotherapy of glioma. In this review, we summarized ROS-based nanomedicine and their application in glioma treatment, including photodynamic therapy (PDT), photothermal therapy (PTT), chemodynamic therapy (CDT), sonodynamic therapy (SDT), radiation therapy, etc. Moreover, the current challenges and future prospects of ROS-based nanomedicine are also elucidated with the intention to accelerate its clinical translation.